1977
DOI: 10.1002/app.1977.070211122
|View full text |Cite
|
Sign up to set email alerts
|

Sorption and diffusion of water in glass ribbon-reinforced composites

Abstract: SynopsisThe processes of sorption and diffusion of water in anisotropic glass ribbon-reinforced composite films of controlled structural and physical characteristics were investigated in terms of the film properties, e.g., geometry, orientation, and volume fraction of the filler; molding characteristics of the composite film; and the adhesion between the glass ribbon and continuous cellulose acetate matrix. While the diffusion of water through unfilled cellulose acetate film was found to be a simple activated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

1981
1981
2006
2006

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 3 publications
0
14
0
Order By: Relevance
“…The one-dimensional diffusion process taking place through two large opposite faces of a solid slab material ( Figure 1 Equation (5) can be rewritten for the case of composites containing a highly permeable fibre phase, as As reported by Bonniau and Bunsell, all the plots represented by equations (5), (6.a) and (6.b) merge into one line during the initial part of the diffusion process, so that this initial linear part of the diffusion curve can well be used to evaluate the concentration independent composite diffusion coefficient. Now, equation (6.b) can be rewritten as,…”
Section: Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…The one-dimensional diffusion process taking place through two large opposite faces of a solid slab material ( Figure 1 Equation (5) can be rewritten for the case of composites containing a highly permeable fibre phase, as As reported by Bonniau and Bunsell, all the plots represented by equations (5), (6.a) and (6.b) merge into one line during the initial part of the diffusion process, so that this initial linear part of the diffusion curve can well be used to evaluate the concentration independent composite diffusion coefficient. Now, equation (6.b) can be rewritten as,…”
Section: Theorymentioning
confidence: 99%
“…Bonniau and Bunsell [4] applied two different diffusion models (single and two phase models) for glass-epoxy composites and concluded that the diamine cured composite obeyed the Fickian diffusion model. Mehta et al [5] reported that glass-ribbon reinforced cellulose acetate films behaved anomalously due to an 290 internal stress phenomenon. They discussed the significance of a structure factor in impermeable fibre based polymer composites.…”
Section: Introductionmentioning
confidence: 99%
“…The sorption and diffusion of low molecular weight substances such as water into polymers is often sensitive to any change in segment mobility or spatial arrangement of polymer chains. 1 For many applications, knowledge of the water absorption properties is important. Natural fibers such as jute are potentially hydrophilic because of the presence of hydroxyl (cellulose) groups.…”
Section: Introductionmentioning
confidence: 99%
“…Pan et al 7 discussed the permeation of water vapor through cellulose membranes. Mehta et al 8 studied the sorption and diffusion of water in glass rubber-reinforced composites, while Sacher and Susko 9 reported the permeation of polyimide films. Some recent studies were conducted on the transport of various organic solvents through rubbery polymers.…”
Section: Introductionmentioning
confidence: 99%